Video analysis platform - Flores, Pablo (2006)
In this article we present the Video Analysis Platform (VAP) which is an open source software framework for video analysis, processing and description. The main goals of VAP are: to provide a multiplatform system which allows the easy implementation of video algorithms, provide structures and algorithms for the segmentation of video data in its different levels of abstraction: shots, frames, objects, regions, etc, permit the generation and comparison of MPEG7-like descriptors, and develop testing applications for shot detection, shot matching, object segmentation and tracking, etc.